Pengenalan Algoritma dan Pemrograman Dasar Berbasis Scratch untuk Menumbuhkan Minat Computational Thinking Siswa SMKN 1 Padarincang - Joko Yuwono; Sefta Tri Wahyuni (LKP KARYA PRIMA KURSUS, 2026)
The low understanding of non-technology Vocational High School (SMK) students toward programming concepts and Computational Thinking (CT) is a challenge in national digital literacy development. This Community Service (PkM) activity aims to introduce algorithms and basic programming using Scratch to foster CT interest among SMKN 1 Padarincang students. The activity was conducted on April 23, 2026, involving 26 Grade X students from the Culinary and Islamic Banking Services (LPS) programs. The method used was a one-day experiential learning-based training using Scratch, covering sequence, selection (if-then), and repetition (loop) concepts. Evaluation was conducted through Pre-Test and Post-Test questionnaires using a Likert scale 1-5 with 10 items. Results showed the average Pre-Test score of 2.12 (Poor category) increased to 4.55 (Excellent category) in the Post-Test, with an average improvement of 114.6%. A total of 96.15% of participants achieved the Excellent category after training. These findings confirm that Scratch is an effective learning medium for introducing programming and CT to non-IT vocational students.